Effect of Land Acquisition and Compensation on the Livelihoods of People in Quang Ninh District, Quang Binh Province: Labor and Income - Tran Tuan NGUYEN; Gábor HEGEDŰS; Tien Long NGUYEN (Land, 2019)
Researchers and development practitioners have an interest in the relationship between land and rural livelihoods. In this context, agricultural land is being increasingly lost because of developing industrialization in the provinces of Vietnam. The livelihoods of people, whose land is appropriated, are affected. Therefore, this article investigates the impact of land acquisition and compensation on the labor and income of people when the State acquires their land to construct Industrial park projects. For the research methods, secondary data from select governmental agencies were gathered, and 50 households were interviewed to collect primary data. The results of this research indicated that although household livelihoods have been reconstructed after land acquisition, many issues are also emerging that may challenge equitable and sustainable development. These include a high proportion of households with insufficient employment, as well as those that are spending compensation money in ways that do not generate income.